Oral iron and the bioavailability of zinc. Issue 6398 (8th October 1983) - Meadows, N J; Grainger, S L; Ruse, W; Keeling, P W; Thompson, R P
Abstract : The oral bioavailability of zinc was studied in nonpregnant adults before and 24 hours after two weeks of oral supplementation with iron and folic acid. Bioavailability was greatly reduced, and the shape of the plasma curves suggested that this was due to impairment of the intestinal absorption of zinc. The findings suggest that the reduced bioavailability of zinc occurs because of interelement competition in the bowel wall. This might induce zinc depletion.